Up-cycling of iron-rich inorganic waste in functional glass-ceramics - Romero, Acacio Rincón; Desideri, Daniele; Boccaccini, Aldo R.; Bernardo, Enrico (Minerals, 2020)
The intensive mechanical stirring of suspensions of recycled glass and inorganic waste powders in ‘weakly alkaline’ aqueous solutions (e.g., 2.5-3 NaOH), followed by viscous flow sintering at 800-1000 °C, easily yields highly porous glass-ceramic foams. The firing determines just the consolidation of powders with concurrent incorporation of pollutants from iron-rich waste, such as fly ash from coal combustion (FA). Engineered mixtures allow for the obtainment of chemically stable foams from treatments in air. Treatments in nitrogen are even more significant since they extend the conditions for stabilization and promote novel functionalities. In addition, the change in the atmosphere favors the formation of magnetite (Fe3O4), in turn enabling ultra-high dielectric permittivity and semiconductivity. Such a condition was further evidenced by preliminary tests on recycled glass combined with residues from the Bayer processing of aluminum ores or red mud (RM).
CRIS-Team Scopus Importer:2020-11-13
Keywords: Alkaline activation; Cellular ceramics; Electrical functionalities; Gel casting; Glass-ceramics; Viscous flow sintering